Regulation of Patent Protection of Computer Programs as Inventions in Indonesia - Asri Sarif; I Gede Mahatma Yogiswara Winatha (Indonesia Law Reform Journal, 2023)
The protection of computer programs in Indonesia has been strictly regulated in the Copyright Law, but the patent obtained by Eddy Tuhirman for his program in 2017 shows that the protection of computer programs in Indonesia is not impossible. This study aims to find out how the regulation of patent protection for computer programs in Indonesia. Using normative juridical research methods, with an emphasis on analysis on applicable legal regulations and other legal sources relevant to the legal issues studied. The results of this study indicate that based on the explanation of Article 4 letter d of Law no. 13 of 2016 concerning Patents, patent protection for computer programs can still be granted on a limited basis. Patent protection is not granted to computer programs which contain only a set of instructions expressed in the form of language, code, schematic or in any other form without having a technical effect. Patents can only be granted for computer programs that have characteristics in the form of instructions, technical effects, and problem solving in the field of technology. In order to provide more legal certainty, it is suggested that the government make stricter and clearer regulations, particularly regarding the types and specifications of computer programs that can be granted patents. Abstrak Perlindungan atas program computer di Indonesia telah diatur secara tegas dalam Undang-Undang tentang Hak Cipta, namun Paten yang didapat oleh Eddy Tuhirman atas program ciptaannya pada tahun 2017 menunjukkan, bahwa perlindungan atas program koomputer di Indonesia bukan sesuatu yang tidak mungkin. Penelitian ini bertujuan untuk mengetahui bagaimana pengaturan perlindungan paten terhadap program komputer di Indonesia. Menggunakan metode penelitian yuridis normatif, dengan menitikberatkan analisis pada peraturan-peraturan hukum yang berlaku dan sumber hukum lainnya yang relevan dengan isu hukum yang diteliti. Hasil penelitian ini menunjukkan bahwa berdasarkan penjelasan Pasal 4 huruf d Undang-Undang No. 13 Tahun 2016 tentang Paten, perlindungan paten atas program komputer masih dapat diberikan secara terbatas. Perlindungan Paten tidak diberikan kepada program computer yang hanya berisi seperangkat instruksi yang diekspresikan dalam bentuk bahasa, kode, skema, atau dalam bentuk apapun tanpa memiliki efek teknis. Paten hanya dapat diberikan untuk program komputer yang memiliki karakteristik berupa instruksi, efek teknis, dan pemecahan masalah di bidang teknologi. Untuk lebih memberikan kepastian hukum, disarankan agar pemerintah dapat membuat peraturan yang lebih tegas dan jelas, khususnya mengenai jenis dan spesifikasi program komputer yang dapat diberikan hak paten.